Advancing students' response to literary texts through the use of literary journals. - Zainal, Zainor Izat; Ali Termizi, Arbaayah; Wan Yahya, Wan Roselezam; Mohd Deni, Ann Rosnida (Malaysian English Language Teaching Association (MELTA), 2010)
Reader-response theory has long been a growing influence in the literature classroom. The theory largely emphasizes the active and communicative role of the reader. Instead of looking at the meaning from within the text, the reader discovers meaning from within themselves, thus negotiates meaning from outside the text. Reader-response theory has evolved in the literature classroom through many practical applications such as role-play, drama, letter writing and literary journals. literary journals are normally adopted in the classroom with the aim of encouraging students to interact with the text and to draw individual responses from it thus moving steadily towards critical appreciation of the text. This study examined the use of literary journals in advancing literary responses among 65 undergraduate students taking English Literature courses at the Faculty of Modern Languages and Communication, Universiti Putra Malaysia. It relied on two types of analyses. Students' responses were coded and categorised using specific response categories to identify the kinds of responses elicited from the students' journals. To find out students' opinion regarding the use of literary journals in improving their responses to and understanding of literary texts, a structured, Likert-scale questionnaire was administered. Findings indicated that literary journals elicited a variety of literary responses from the students. In addition, students' positive feedback confirmed the viability of journal literary s as a practical application tool in the literature classroom.